Defending Dualism - Smythe, Thomas W. (Advances in Social Sciences Research Journal, 2017)
It is the contention of this paper that the arguments in philosophy given both for and against dualism are less than decisive. In this paper I examine some of the standard arguments or objections to dualism, and try to show they are unconvincing. Although I do not think that any good arguments have been given for being a dualist, I shall not pursue that here. Instead, I will engage in a relatively unpopular enterprise of defending dualism against some common objections. I make no claim to cover all of the objections.